O etnodesenvolvimento como questão de justiça ecológica : aliando demandas indígenas à proteção da natureza - Farias, Douglas Loroza (2020)
The justification of the elements that should guide a legal regime that values both the protection of nature and ethnodevelopment is one of the greatest challenges to be faced by Environmental Law nowadays. To this end, the concept of ethnodevelopment is initially exposed, its relationship with the new indigenous demands for integration with the market and its protection, as a result of the broadest protection constitutionally conferred on indigenous cultures. Through this exhibition, the need for Environmental Law to dialogue with the real indigenous and no longer with stereotypes is pointed out. International experiences are then presented, in which Environmental Law establishes a this kind of dialogue, focusing on the American Continent: the greening of the Inter-American System for the Protection of Human Rights and Ecuador's nature rights. These two experiences are complemented by the one occurred in New Zealand, which combines the recognition of the rights of nature with complex structures of business law for the economic exploitation of indigenous territories. The theoretical framework of ecological justice with a focus on capabilities, by Schlosberg, is presented, relating the dimension of recognition of this theory of justice with the negotial aproach to self-determination of indigenous peoples and with the content of art. 231 of the Brazilian Constitution. The protection of ecological integrity through a curator State, also arising from this theoretical framework, is related to the duty to protect art. 225. Finally, it is concluded that ecological integrity is both a condition and a limiting factor for ethnodevelopment and that an ethnodevelopment that respects ecological integrity may give rise to different interpretations of the idea of conservation: ethnoconservation¸ which should be encouraged, especially in indigenous territories, by the pluralist spirit of the Brazilian Constitution.